Flexible Vision - The Application and Expansion of Constitutive Language in Visual Communication Design - Wang, Dan (Transactions on Social Science, Education and Humanities Research, 2023)
With the deepening of China’s economic system reform and the rapid development of higher education, the employment model provides modern talents with space for freedom to soar, and puts forward higher requirements. Modern society requires professional talents with all-round development, so it is crucial to develop a relatively complete education and teaching model that meets the needs of social development. As a researcher on the composition system of visual communication design discipline, after years of study and research in the design major, I have found that the art of composition in basic design courses is a good entry point. Studying its visual expression patterns in different time and space (plane, space, dynamic) can form a complete visual communication design discipline system, making design truly an important driving force for China’s economic development.